Secondary Metabolite Ceiba pentandra Gaertn. as Biological Control to Canker Disease on Dragon Fruit - Masnillah, Rachmi; Budi, Ival Oktavian Nurtian; Pradana, Ankardiansyah Pandu; Alfarisy, Fariz Kustiawan (Journal of Tropical Life Science, 2021)
Canker diseases caused by Neoscytalidium dimidiatum are a serious threat for dragon fruit production.Â Comprehensive and environmentally friendly control efforts are needed to reduce yield losses due to this disease. Cottonwood (Ceiba pentandra) is one of the plants that contain complex phytochemicals that can control phyto-pathogens. This study aimed to examine the potential of secondary metabolites produced from the leaves and bark of the C. pentandara as botanical fungicides. Parts of dragon fruit that are attacked by canker are isolated on Potatoes Dextrose Agar media. Observation of conidia and fungal spores using a binocular microscope with a magnification of 100Ã—. The hyphal form of the N. dimidiatum is rectangular and clear. As botanical fungicides, the leaves and the bark of the C. pentandara are dried for 14 days. The extract solution then analyzed for itâ€™s secondary metabolites. The results of the qualitative analysis showed that each leaf extract and bark (+) compound of flavonoids, alkaloids, tannins, and saponins. The quantitative results of secondary metabolites detected 304.3 mg.kg-1, Flavonoids and Tannins of 1.6 mg.kg-1. Secondary metabolites obtained were tested on the fungus N. dimidiatum with inhibitory parameters in vitro and in vivo. This study followed a factorial completely randomized design consisting of concentration factors and types of extract parts. The data obtained were then analyzed by ANOVA and significant treatments were further tested by Duncan Multiple Range Test (DMRT) at Î± = 5%. The combination treatment with a concentration of 40 mg ml-1 is more effective in controlling canker in indicators of inhibitory, the extent of the attack, and intensity of disease severity.